2014
DOI: 10.1021/jp508813n
|View full text |Cite
|
Sign up to set email alerts
|

Role of Charge and Solvation in the Structure and Dynamics of Alanine-Rich Peptide AKA2 in AOT Reverse Micelles

Abstract: The propensity of peptides to form α-helices has been intensely studied using theory, computation, and experiment. Important model peptides for the study of the coil-to-helix transition have been alanine–lysine (AKA) peptides in which the lysine residues are placed on opposite sides of the helix avoiding charge repulsion while enhancing solubility. In this study, the effects of capped versus zwitterionic peptide termini on the secondary structure of alanine-rich peptides in reverse micelles are explored. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In more recent work, we calculated IR spectra of AKA 2 peptides in spherically restrained and unrestrained RMs. 35 The computed spectra were in good agreement with experimentally measured spectra for AKA 2 peptides in RMs. 17 The results validate our simulation model of AOT RMs and suggest that probing the features of these complex systems using simulation studies is an essential complement to experiment.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In more recent work, we calculated IR spectra of AKA 2 peptides in spherically restrained and unrestrained RMs. 35 The computed spectra were in good agreement with experimentally measured spectra for AKA 2 peptides in RMs. 17 The results validate our simulation model of AOT RMs and suggest that probing the features of these complex systems using simulation studies is an essential complement to experiment.…”
Section: Introductionsupporting
confidence: 79%
“…34,35,49,50 For our simulations of Aβ 16−22 in AOT RMs, Figure 2 shows the average number of molecules (AOT head groups, AOT tail groups, and sodium ions) within 4 Å of each amino acid side chain of the monomers and dimers, respectively. The number of interactions for the peptides does not change significantly between the monomer and dimer systems, and in both systems there are significant hydrophobic interactions between the V 18 FFA 21 of the Aβ 16−22 peptides and the AOT tail groups.…”
Section: Resultsmentioning
confidence: 99%
“…The MD simulations of Straub and co-workers 67 provided further atomistic details of the above-mentioned peptide system in spherically restrained and unrestrained RMs of w 0 = 6. They found that α-helical structure was stable under both conditions, consistent with the experimental observation.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…MD snapshots of an alanine-based peptide in a spherically restrained (left, pink) and a spherically unrestrained (right, green) RM, showing the interaction between the peptide, the surrounding water molecules (blue), and the AOT tail groups (gray). Reprinted with permission from ref . Copyright 2014, American Chemical Society.…”
mentioning
confidence: 99%
“…Tian and Garcia explored the dynamics and location of proteins in RMs 39 and the effect of RMs on the ubiquitin structure and dynamics. 40 Straub and co-workers explored the effect of charged and zwitterionic termini on a RM-spanning protein on the structure and dynamics of RMs 41 as well as the effect of RM-encapsulation on amyloidogenic peptide aggregation. 42 Eskici and Axelsen also investigated the role of RM-encapsulation on the structure of amyloid beta.…”
Section: Introductionmentioning
confidence: 99%